أحكام العبادات الخاصة بالمتضررين من الفيضانات: دراسة فقهية تحليلية = The rules of worships (Ibadat) for those affected by floods: a juristic analytical study - Mohd Noor, Mohd Izzuddin; Mat Jubri@Shamsuddin, Mustafa (IIUM Press, International Islamic University Malaysia, 2018)
This research addresses floods and how they affect the rules of worship (Ibadah) such as cleansing of oneself (Taharah), prayer (Salah), fasting (Sawm), alms (Zakah) and pilgrimage (Hajj). As much as the rules of Shariah relate to the acts of Mukallafin (who are legally competent to be responsible for religious duty), the effect of this kind of disaster reflects in the rules of victims’ actions, in terms of its obligation or not. The research confirms that floods are among the reasons that allow for the rule of reduction, ease and exemption from some parts of obligation in Islam (Rukhsah), because the situation is inconvenient and unbearable for the victims due to the hardship and necessity. So, considering their state of necessity, the rules of Fiqh related to worship will be based on these maxims: “Prevention and Eradication of Harm” and “Consideration of Ease and Reduction of Burden”. The inductive methodology is applied in the research by generating and collecting data from the sources, as well as the analytical methodology by analyzing the views of Islamic jurists on the topic. One of the main findings of the research is that floods have some adverse effects, such as bringing harm and damage to the people, putting the victims in a situation of unrest due to hardship and difficulty. In fact, the victims may be in the state of necessity; if some lives are lost. The victims of this disaster are permitted to use rules of Rukhsah in their worships, provided that hardship and necessity occur, and so that the removing and eradicating hardship and difficulty are required. This verdict is based on Shariah evidences such as the rule of analogy (Qiyas), means (Dharai') and unrestricted interests (Masalih Mursalah).